2014
DOI: 10.1016/j.ijpe.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting foundations in lot sizing—Connections between Harris, Crowther, Monahan, and Clark

Abstract: While many review articles exist on (deterministic) lot sizing models used in the context of price and quantity discounts, buyer-vendor coordination, supply chain management, and joint economic lot sizing problems, they do not convey the impact of important findings which date back to at least 2002, or, in hindsight, to 1984. As a result, many recent articles still model the financial implications of lot sizing decisions without having the assurance that these models would help the firm(s) involved in maximis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…Second, a model only based on cost will also prove difficult for accurately deriving the NPV function of the supplier since part of the costs of the retailer will translate into revenues for the supplier, and hence the need for considering the revenue stream for the supplier, too. See also Beullens [26] for a discussion on the impact that a lack of recognition of revenues shifting over time has had on inventory research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, a model only based on cost will also prove difficult for accurately deriving the NPV function of the supplier since part of the costs of the retailer will translate into revenues for the supplier, and hence the need for considering the revenue stream for the supplier, too. See also Beullens [26] for a discussion on the impact that a lack of recognition of revenues shifting over time has had on inventory research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A literatura envolvendo PDLé bastante vasta. Revisões bibliográficas de trabalhos que estudam PDL podem ser encontradas desde os trabalhos de Billington et al (1983), Bahl et al (1987), até mais recentemente, Karimi et al (2003), Glock et al (2014), Holmbom e Segerstedt (2014), Beullens (2014) e Brahimi et al (2017).…”
Section: Introductionunclassified
“…Each of these factors may have important influences on the total costs and overall performance of the production plan. Reviews of different aspects of lot sizing problems can be found, for example, in Karimi et al (2003), Brahimi et al (2006), Degraeve (2007, 2008), Robinson et al (2009), Glock et al (2014), Holmbom and Segerstedt (2014) and Beullens (2014).…”
Section: Introductionmentioning
confidence: 99%